Recurrent CIC-rearranged sarcoma of central nervous system: a clinicopathological case report - Jiang, Shan; Li, Kay Ka-Wai; Hu, Jingqi; Guan, Yun; Zhu, Rui-Ze; Xu, Hou-Shi; Sun, Mao-Yuan; Liu, Bei-Ning; Chai, Hui-Hui; Wang, Yue; Tang, Qi-Sheng; Ng, Ho-Keung; et al. (Frontiers in Oncology, 2026)
CIC-rearranged sarcoma (CRS) is a subgroup of small round blue cell tumors similar to Ewing’s sarcoma but lacking the EWSR1 gene translocation. It is characterized by a CIC gene rearrangement on chromosome 19q13, with the most common partner gene being DUX4. In 2021, the WHO classification of central nervous system tumors (5th edition) introduced a new pathological classification for CRS based on bone and soft tissue tumor classifications, categorizing it as mesenchymal non-meningeal epithelial tumors. Primary CIC::DUX4 rearrangement sarcoma in the central nervous system is extremely rare, with no established standard treatment and a very poor prognosis. Herein, we present a case of intracranial CIC::DUX4 rearrangement diagnosed using DNA methylation classifiers and multiple omics diagnosis techniques. We also document the disease progression after chemoradiation therapy and subsequent in situ recurrence.